Intervention to improve management of acute hepatitis C infection in a UK sexual health clinic. (February 2018) - Tomkins, A; Lee, V
A case note review was conducted for all newly-diagnosed acute hepatitis C virus (HCV)-infected patients attending our sexual health clinic pre- and post-implementation of an HCV clinic proforma between January 2010 and September 2016. In total, 87 patient notes were included (40 pre-intervention, 47 post-intervention) of whom 81 were HIV-positive. Data were collected regarding documentation of the following: baseline investigations, four-weekly HCV viral load monitoring, risk assessment, partner notification, advice given and Public Health England (PHE) notification. Appropriate baseline investigations, four-weekly monitoring of HCV viral loads, risk assessment and advice documentation all improved in the post-intervention group when compared to pre-intervention. PHE notification and partner notification remained below the national standard post-intervention, with educational measures among relevant staff implemented accordingly. This audit demonstrates improvement across several key areas post clinic proforma implementation.